Attitudinal Disposition of Students Towards the Personality Traits of Counsellors. A Case Study of Public Secondary Schools in Delta State, Nigeria - Obiunu, Jude J.; Rachael, Ozuri (International Journal of Emerging Trends in Social Sciences, 2018)
The study examined attitudinal disposition of students towards the personality traits of counsellors, using a case study of Public Secondary Schools in Delta Central Senatorial District of Delta State. The descriptive survey design was adopted for the study. 1 research questions and 2 hypotheses were formulated to guide the study. The population for this study consists of all the students in all the public senior secondary schools in Delta Central Senatorial District. A sample size of 2000 students were randomly selected from all the schools in the senatorial district. The instrument for the study was a questionnaire titled Attitudinal Disposition of Students towards Personality Traits of Counsellors (ADSPTC). The instrument had a reliability value of 0.85. Simple percentage, mean and standard deviation were used to answer the research questions while t-test statistics of independent sample was used to test the hypotheses at 0.05 level of significance. The result revealed that student’s attitudinal disposition towards the personality traits of counsellors is negative, that there was no significant difference in the attitudinal disposition of students towards the personality traits of counsellors based on gender also there was a significance difference in the attitudinal disposition of students towards the personality traits of counsellors based on location. It was however recommended that counsellors should exhibit the professional qualities such as kindness, empathy, unconditional positive regard, genuiness, patience and love towards students. Counsellors should also not be biased in rendering their services and should accept every students unconditionally irrespective of gender and location.